La catalogación de los apuntes de teatro en la biblioteca histórica municipal - Aguerri Martínez, Ascensión (Revista General de Información y Documentación, 2007)
The theatre and music collection of the Municipal Historic Library contains one of the most important sources of study for music, theatre and stage art for the 18th and 19th century. It was placed in catalogs, however incompletely, between 1898 and 1902, by a small group of librarians in the municipal library system headed by Mr. Carlos Cambronero. For a long time now the collection is believed to be in need of a more complete description including all the works. In order to adopt the ideal format for describing the complete collection it is believed necessary to analyze the context in which these works were produced. The theatre stagenotes (apuntes de teatro), sketchbooks, manuscripts or prints, which contain in addition to the dramatic text, the stagenotes or instructions for staging of a theatre piece form this collection. This material was used by actors` aids , the director of the company or sometimes the main actor or producer. The peculiar characteristics of this collection of dramatic pieces pose problems for the cataloguing of the work. Examples of the descriptions given to this type of work has been placed forth in order to highlight the problem.
Keywords: Stagenotes for theatre; Historic Municipal Library of Madrid; Spanish Theatre; Spanish Music; Staging of works; Cataloging of special materials